The Effect of a Market Orientation on Business Profitability - Narver, John C.; Slater, Stanley F. (Journal of Marketing, 1990)
Marketing academicians and practitioners have been observing for more than three decades that business performance is affected by market orientation, yet to date there has been no valid measure of a market orientation and hence no systematic analysis of its effect on a business's performance. The authors report the development of a valid measure of market orientation and analyze its effect on a business's profitability. Using a sample of 140 business units consisting of commodity products businesses and noncommodity businesses, they find a substantial positive effect of a market orientation on the profitability of both types of businesses.